Experimental investigation of stabilisation of soils with Taftan pozzolan. Issue 9 (28th July 2020) - Toufigh, Vahid; Barzegari Dehaji, Mohammad; Jafari, Khashayar
Abstract: Portland cement releases a large amount of greenhouse gases and affects the environment in a negative way. An attempt has been made to use geopolymer instead of cement for soil stabilisation due to its excellent properties such as high mechanical behaviour, low cost, low energy consumption and less production of dioxide carbon production. In this study, a new stabilising material 'Taftan pozzolan' was used along with different concentrations of the activator, to improve the mechanical behaviour of soil. The stabilised specimens were tested under uniaxial compression loading at different curing periods. Furthermore, SEM and XRD were used to determine the microstructure analysis and chemical composition of the specimens, respectively. Results indicated that the compressive strength of stabilised soil increased up to 30 times as compared to the soil specimen. The comparison between the cement stabilised soil and ASN specimens showed that the compressive strength of geopolymer specimen was 11% higher than that of the cement, and cement produces 300% more carbon dioxide than ASN specimen. Furthermore, Taguchi method was used to determine the optimum conditions for the compressive strength. Based on this investigation, the Taftan pozzolan can be considered as an appropriate material for applications due to its excellent characteristics.